Pavlov’s Irkutsk: Preserving the legacy of Soviet modernism - Grigoryeva, Elena; Saprykina, Natalia; Timofeev, Sergey; Druzhinina, Inna; Zolotareva, Milena; Makarov, Andrey; Eremin, Nikita; Antipin, Konstantin; Sharygin, Alexander; Khotulev, Ruslan; Chertilov, Alexey; Zykov, Evgeny; et al. (project baikal, 2025)
The Architecture Department of the Russian Academy of Architecture and Construction Sciences, the International Academy of Architecture (Moscow Branch, IAAM) and the PROJECT BAIKAL journal held a round table discussion “Pavlov’s Irkutsk: Preserving the legacy of Soviet modernism” at the XXV Interregional Festival ZODCHESTVO IN SIBERIA on September 5. In May 2025, the Russian branch of ICOMOS included the preservation of “Pavlov’s Modernism” in Irkutsk in the list of the most urgent and significant problems.
Keywords: neo-brutalism; cultural heritage sites; V. A. Pavlov; VOOPIK; architecture; modernism; preservation